Study Of Water Distribution Patterns and Temperature Changes in Waters Around Power Plant (Case Study of PLTU Tanjung Jati B Unit 5 & 6) - Mukhtasor; Fajar Lemanza Djazuli; Shade Rahmawati (International Journal of Offshore and Coastal Engineering, 2025)
Sea cooling discharge refers to heated wastewater produced during the operational of a Steam Power Plant (PLTU). This effluent is typically discharged into the sea via an ocean outfall, a process that can significantly impact the surrounding marine environment and ecosystems. One of the primary consequences of this discharge is the elevation of seawater temperature in the vicinity of the outfall. This study aims to analyze the distribution patterns and temperature increases of seawater around the ocean outfall of Tanjung Jati B Power Plant Units 5 & 6. Numerical modeling was conducted using the Delft3D software, employing both the FLOW and WAVE modules to simulate the dispersion of thermal effluent and to assess temperature variations under different environmental conditions. The simulation results show that, during the west monsoon, the dispersion of thermal effluent predominantly extends toward the northeast, while during the east monsoon, the dispersion is mainly directed toward the west, northwest, and north. These findings underscore the significant influence of ocean currents and waves on the distribution of thermal effluent. Additionally, the maximum observed temperature increases of the thermal effluent reached 9°C, with the average area experiencing a temperature rise greater than 2°C measured at 932.16 m² during the west monsoon and 1,487.62 m² during the east monsoon, when comparing the 2024 dispersion pattern to the baseline seawater temperature in 2015. To mitigate the spread of thermal effluent, three alternative solutions are proposed: (1) extending the outfall structure, (2) evaluating and optimizing the design of the existing outfall. There are several potential approaches to minimize the dispersal of thermal wastewater, but further study is required to evaluate the effectiveness of these solutions.